Reemergence of St. Louis Encephalitis Virus in the Americas - Diaz, Adrián; Coffey, Lark L.; Burkett-Cadena, Nathan; Day, Jonathan F. (Emerging infectious diseases, 2018)
We summarize and analyze historical and current data regarding the reemergence of St. Louis encephalitis virus (SLEV; genus Flavivirus) in the Americas. Historically, SLEV caused encephalitis outbreaks in the United States; however, it was not considered a public health concern in the rest of the Americas. After the introduction of West Nile virus in 1999, activity of SLEV decreased considerably in the United States. During 2014-2015, SLEV caused a human outbreak in Arizona and caused isolated human cases in California in 2016 and 2017. Phylogenetic analyses indicate that the emerging SLEV in the western United States is related to the epidemic strains isolated during a human encephalitis outbreak in Córdoba, Argentina, in 2005. Ecoepidemiologic studies suggest that the emergence of SLEV in Argentina was caused by the introduction of a more pathogenic strain and increasing populations of the eared dove (amplifying host).